2016
DOI: 10.1039/c5dt04977f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of [(HPO3)6Mo21O60(H2O)4]8−: a new redox active heteropoly blue cluster with layered shape containing a phosphite template that self-assembles under controlled microwave irradiation

Abstract: The microwave-driven synthesis of a heteropoly blue cluster yields a redox active cluster, [(HPO3)6Mo21O60(H2O)4](8-), templated by six phosphite anions whereby two phosphites template a tri-lucunary {Mo15} Dawson structure, and one templates a {Mo6} ring with two of the three remaining phosphites acting as bridging ligands connecting the ring to the {Mo15}.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Yan and co-workers used microwaves to synthesize POMs out of sodium molybdate. 13,14 In a solid-state synthesis, the Keggin-type POM as K 3 PM 12 O 40 (M = Mo, W) could be synthesized via heating a mixture of MO 3 , K 2 CO 3 and K 2 HPO 4 at 500 • C for 30 h. 15 In the last decade mechanochemistry has gained a lot of interest as a synthetic method. The term is used for chemical reactions induced by mechanical energy and performed in hand mortars as well as ball, planetary and vibration mills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan and co-workers used microwaves to synthesize POMs out of sodium molybdate. 13,14 In a solid-state synthesis, the Keggin-type POM as K 3 PM 12 O 40 (M = Mo, W) could be synthesized via heating a mixture of MO 3 , K 2 CO 3 and K 2 HPO 4 at 500 • C for 30 h. 15 In the last decade mechanochemistry has gained a lot of interest as a synthetic method. The term is used for chemical reactions induced by mechanical energy and performed in hand mortars as well as ball, planetary and vibration mills.…”
Section: Introductionmentioning
confidence: 99%
“…Yan and co-workers used microwaves to synthesize POMs out of sodium molybdate. 13,14 In a solid-state synthesis, the Keggin-type POM as K 3 PM 12 O 40 (M = Mo, W) could be synthesized via heating a mixture of MO 3 , K 2 CO 3 and K 2 HPO 4 at 500 °C for 30 h. 15 …”
Section: Introductionmentioning
confidence: 99%
“…However, microwave-assisted synthesis has received little attention in the synthesis of POMs . In 2016, our group obtained a heteropoly blue, [(HPO 3 ) 6 Mo 21 O 60 (H 2 O) 4 ] 8– , by using a microwave-driven method . However, when traditional heating was used, reduced Keggin-type POM [PMo 12 O 40 ] 4– was obtained instead.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Reports about polyoxometalates synthesized through microwave irradiation are few but meaningful;i th as provided an ew way of thinking in polyoxometalate synthesis, [32] and chemical reactions under microwave assistance have been proved to be efficient and ecofriendly. [31] Reports about polyoxometalates synthesized through microwave irradiation are few but meaningful;i th as provided an ew way of thinking in polyoxometalate synthesis, [32] and chemical reactions under microwave assistance have been proved to be efficient and ecofriendly.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has found that am icrowave-assisted synthesis methodi sa ne ffective way for producingn ew POMs by embedding redox active templates into the polyoxometalate framework in our previous work. [31] Reports about polyoxometalates synthesized through microwave irradiation are few but meaningful;i th as provided an ew way of thinking in polyoxometalate synthesis, [32] and chemical reactions under microwave assistance have been proved to be efficient and ecofriendly. [33][34][35] 6 ]·12 H 2 O( 1)w ith sandwich-type structure.…”
Section: Introductionmentioning
confidence: 99%